Left ventricular mass - a facade for left ventricular calcification - Halkati, Prabhu; Patted, Suresh; Modi, Ranjan (International Journal of Research in Medical Sciences, 2016)
Calcification overlying the left side of the heart on a chest radiograph may involve either the pericardium or, alternatively, the myocardium in association with a left ventricular aneurysm. Pericardial calcification was found primarily over the right-sided cardiac chambers and in the atrioventricular grooves, infrequently over the base of the left ventricle, and rarely over the apex of the left ventricle. When the left ventricle was involved, there was always more extensive calcification elsewhere in the pericardium. Myocardial calcification occurred predominantly in the apex of the left ventricle, although it was rarely confined to the posterior wall of the left ventricle. Isolated calcification in the region of the left ventricular apex, therefore, strongly suggests left ventricular aneurysm. Isolated idiopathic left ventricular calcification without any detectable abnormality is a rare phenomenon and found to be worth reporting.